Assessment of Staphylococcal Contamination in Traditional Yogurt Around Kabul City - Ahmadi, Seyed Arif (Journal of Natural Sciences – Kabul University, 2021)
Yogurt, a universally consumed dairy product, is rich in nutrients but also provides a conducive environment for microbial activity. If proper hygiene is not maintained during its production, storage, and distribution, it can become a source of staphylococcal poisoning. This study involved the random collection of yogurt samples from various locations in Kabul City to assess contamination by Staphylococcus species. Samples were transported under sterile conditions to the Research Laboratory in Darulaman for analysis. Suspected colonies were cultured on Baird-Parker agar and MacConkey agar, stained, and subjected to biochemical tests such as the catalase test. The findings revealed that 20% (4 out of 20) of the yogurt samples were contaminated with Staphylococcus species. The study concludes that yogurt contamination arises from multiple factors, necessitating improved public health measures to ensure safety.